The 5-minute neurology consult - Lynn, D. Joanne; Newton, Herbert B.; Rae-Grant, Alexander (The s-minute series, 2012)
"We are pleased to bring a second edition of the Neurology volume to the 5-Minute Consult series. This book is intended to present current clinical information to several groups: - Busy clinical practitioners in neurology general practice, emergency rooms, and non-neurologic specialties who need a reference source where they can quickly refresh their knowledge about the basics of a neurologic condition - Residents and students seeking rapid access to basic data about diagnosis and treatment for various neurologic conditions - Patients and families who want quick information about their diagnoses and referrals to patient information sources and support organizations Neurology is an area of medicine that incites anxiety and discomfort for many students, nurses, and physicians who have not trained in the specialty. Effective therapeutic interventions continue to expand and flourish; every practitioner must understand the diagnosis and treatment of basic neurologic conditions. Information is provided in a structured format that allows easy access and rapid assimilation. We have attempted to offer relevant and current references. We hope that this rapid information source will help all to approach patients suffering from neurologic disorders with more confidence. "--Provided by publisher.